Predicting time of death by postmortem erythrocyte osmotic fragility test in Sprague-Dawley white mouse - Beta Ahlam Gizela Beta Ahlam Gizela (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: Death cases caused by crime require estimation of the time of death as a guide for searching who is the murderer. The common method has been used is by detecting hypostasis, rigidity, temperature decreasing, and decomposition. These methods are less accurate, since they are influenced by various factors. A new more accurate method is, therefore, required.Objectives: To establish a new method in predicting time of death by searching for relations between erythrocyte osmotic fragility and time of death.Methods: This research used Quasi Experiment Design. The subjects were 31 white male of mice 2 months old. The mouse blood was taken in a periodic time: ante mortem, 0, 1, 2, and 3 hours postmortem, and their erythrocyte osmotic fragility was detected by Modification Method of Osmotic Fragility Test. The reagent used was Saline Buffer Phosphate in gradual concentration, 0.2%, 0.3%, 0.4%, 0.5%, and 0.6%.Results: Data taken from this research were analyzed by regression analysis and ROC curve analysis.There was a significant positive correlation between time of death and erythrocyte osmotic fragility (r2 = 0.536, p< 0.01). Erythrocyte osmotic fragility of 0.5% (under curve area=0.826, p<0.01) was a cut off point at 1.5  hours post mortem (MSS=154.4%).Conclusion: Post mortem erythrocyte osmotic fragility test have a value in predicting time of death.Erythrocyte osmotic fragility test of 0.5% occured at      1.5  hours post mortem.Keywords: time of death - post mortem - erythrocyte osmotic fragility